Análise teórico-experimental da difusividade térmica em material opaco utilizando o Método Flash - Vilar, Diego Dantas Queiroz (2012)
This work proposes the thermal characterization of an opaque solid using the Flash Method as an estimation technique of thermophysical properties. Thermal characterization corresponds to the identification of heat transfer properties. The properties that most interest among researchers are: specific heat, thermal capacity, conductivity and thermal diffusivity. The characterization techniques have been evolving in parallel with the rise of new materials, as well as the necessity and accuracy of the intrinsic characteristics of each one. The use of the equations of heat and mass transfer is subject to the availability of data on the intrinsic characteristics of the materials involved, the thermophysical properties in particular. Estimates of energy exchange can be performed from the values of density, thermal diffusivity, specific heat and thermal conductivity of materials. In this context, there are countless failures in thermal projects by the unavailability of reliable data of thermodynamic and transport properties of the studied object. It is proposed in this research a numerical analysis, comparing it with experimental data on thermal characterization. Among the available experimental techniques, a transient pulse method was chosen, in particular, the Flash method, universally recognized for its accuracy and easy usage. Results are presented in terms of thermal diffusivity, thermal conductivity and specific heat.